2019
DOI: 10.1111/codi.14910
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of preoperative versus postoperative transversus abdominis plane and rectus sheath block in patients undergoing minimally invasive colorectal surgery

Abstract: Aim Ultrasound-guided transversus abdominis plane and rectus sheath block (TAPRSB) decreases pain scores and narcotic use postoperatively after colorectal surgery (CRS). It is unclear if the effectiveness of TAPRSB varies according to whether it is performed preoperatively or postoperatively. Our aim was to investigate this.Method We compared patients who underwent preoperative TAPRSB or postoperative TAPRSB during minimally invasive CRS. Primary end-points were pain scores and oral morphine milligram equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The usage frequencies and doses of the rescue analgesic drugs were recorded. Cumulative IV opioid consumption was calculated from the dose conversion of fentanyl, tramadol, and pethidine into morphine according to the equivalent analgesic dose ratio (i.e., 100 μg of fentanyl = 100 mg of tramadol = 100 mg of pethidine = 10 mg of morphine) [13][14][15], and assessed at 1, 6, and 24 h after surgery.…”
Section: Opioid Administrationmentioning
confidence: 99%
“…The usage frequencies and doses of the rescue analgesic drugs were recorded. Cumulative IV opioid consumption was calculated from the dose conversion of fentanyl, tramadol, and pethidine into morphine according to the equivalent analgesic dose ratio (i.e., 100 μg of fentanyl = 100 mg of tramadol = 100 mg of pethidine = 10 mg of morphine) [13][14][15], and assessed at 1, 6, and 24 h after surgery.…”
Section: Opioid Administrationmentioning
confidence: 99%
“…The paravertebral block has been shown to be superior to other locoregional analgesic techniques for the management of perioperative pain [ 9 , 10 ]. Furthermore, although the timing of nerve blockade in patients undergoing gynecological, breast, gastrointestinal, and plastic surgeries has been discussed previously [ 11 , 12 ], few studies have investigated the optimal intraoperative analgesia strategy, including ICB, for TS. Therefore, in this study, the divided method of ML-ICB (at the beginning and the end of surgery) was selected to compensate for the inferior effect of ICB in the management of perioperative pain since locoregional analgesia is delivered before the patient experiences pain (preemptive anesthesia).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that a preoperative block for an extremity amputation may reduce the incidence of phantom limb pain [ 6 ]. For transversus abdominis plane (TAP) blocks specifically, there is no clear evidence of increased effectiveness if done preoperatively versus postoperatively [ 7 , 8 ]. Difficulty in performing the procedure may impact overall procedure time, leading to potential OR delays, prolonged OR time, or prolonged patient discomfort if performed post-emergence.…”
Section: Discussionmentioning
confidence: 99%